Comparison of indoor temperatures of homes with recommended temperatures and effects of disability and age: an observational, cross-sectional study. Issue 5 (14th May 2018) - Huebner, Gesche M; Hamilton, Ian; Chalabi, Zaid; Shipworth, David; Oreszczyn, Tadj
Abstract : Objectives: We examine if temperatures in winter in English homes meet the recommendation of being at least 18°C at all times. We analyse how many days meet this criterion and calculate the hours per day and night being at/above 18°C. These metrics are compared between households with occupants aged above 64 years or having a long-term disability (LTD) and those younger and without disability. Design: Cross-sectional, observational. Setting: England. Participants: 635 households. Outcomes measures: (1) Mean temperatures, (2) proportion of days of the measurement period meeting the criterion, (3) average hours at/above 18°C, (4) average hours at night at/above 18°C. Results: Mean winter temperatures in the bedroom were MBR =18.15°C (SD=2.51), the living room MLR =18.90°C (SD=2.46) and the hallway MHall =18.25°C (SD=2.57). The median number of days meeting the criterion was 19–31%. For the living room, more days meet the criterion in the group with a LTD (Mdisability =342 vs Mno_disability =301, 95% CI 8 to 74), and with someone over 64 years present (Mabove64 =341, Mbelow65 =301 95%, CI 8 to 74). The median number of hours/day meeting the criterion was 13–17. In the living room, households with a disability had more hours at 18°C (Mdisability =364, Mno_disability =297, 95% CI 17 to 83) as did the older age group (Mabove64 =347, Mbelow65 =296, 95% CI 18 to 84). In the hallway, more hours met the criterion in households with a disability (Mdisability =338, Mno_disability =302, 95% CI 3 to 70). 247 homes had at least nine hours of at least 18°C at night; no effect of age or disability. Conclusions: Many households are at risk of negative health outcomes because of temperatures below recommendations.